Steroid withdrawal or avoidance in renal transplant recipients - Chang, S.H.; Tan, Si Yen (Faculty of Medicine, University of Malaya, 2006)
Steroids remain an important component of maintenance immunosuppression after renal transplantation. Their anti-inflammatory action is partly due to the sequestration of CD4+ lymphocytes in the reticuloendothelial system. Steroids bind to intracellular receptors and the resulting steroid-receptor complex alters the transcription of cytokines by binding to glucocorticoid response elements on DNA. Transcription factors whose actions are altered by glucocorticoids include activating protein-1 (AP-1) and nuclear factor-κB (NF-κB). The main cytokines whose production by antigen-presenting cells is inhibited by steroids are interleukin-1 (IL-1), required for helper T-cell activation, and IL-6, required for B-cell activation. Other pro-inflammatory cytokines such as interferon gamma and tumour necrosis factor are also inhibited. This multiplicity of immunosuppressive actions is not fully replicated by other immunosuppressants. However, there are concerns about the long-term side effects of steroids. This review will examine the attempts at steroid withdrawal or steroid avoidance in renal transplant patients.